<span>P: y + z = 6
Q: 8y + 7z = 1
A. This makes y = -8Y which will eliminate the "y"'s when the equations are added.
</span>
Answer:
<h2>a=V⅓=1728⅓≈12</h2><h2 />
Step-by-step explanation:
<h2>Using the formula</h2><h2>V=a3</h2>
<h2>it is right answer </h2><h3>hope it will help you </h3>
Y=x-2+3
I put x-2 because when graphing it's the opposite so it would technically be x+2
Then the +3 for the y chords which go up by 3 ! if this is wrong then try Y= (x-2)+3
Answer:
Step-by-step explanation:
Given
A circular ring
Required
The length
Let
the radius of the ring
The length is calculated by calculating the circumference of the ring.
This is calculated using:
or
Where
diameter
and
It is a composite number and it is written as 7*3*5*2